Positioning control of a flexible slewing structure by applying sliding mode control - Janzen, Frederic Conrad [UNESP]; Tusset, Angelo Marcelo; Balthazar, Jose Manoel [UNESP] (My University, 2016)
This work presents the angular positioning control of a flexible beam like structure connected to the shaft of a DC (Direct Current) motor. The coupling between the flexible structure and the DC motor is considered as not ideal being that the structure model considers three vibration modes. A nonlinearity known as death zone is included in the DC motor model. To control the angular position a Sliding mode controller is proposed and the influence of the control gains is analyzed numerically. Numerical simulations will be presented to demonstrate the application of the sliding modes technic in order to control the positioning of the flexible link by controlling the DC motor armor current.